Assessment of Respiratory Symptoms among Sandstone Workers Associated with Respirable Dust and Fine Particulate Matter (PM2.5) Exposure - Wirot Chanthorn; Laksana Laokiat (Universitas Airlangga, 2025)
Introduction: Sandstone workers were exposed to dust generated during processing. This research aimed to determine the concentrations of respirable dust (RD) and fine particulate matter (PM2.5), as well as to assess respiratory symptoms and associated factors. Methods: A cross-sectional study was conducted among 140 sandstone workers in northeastern Thailand. Personal dust samples were collected throughout the shift in accordance with NIOSH 0600 and EPA IP-10A. The dust concentrations were analysed by the gravimetric method. Face-to-face interviews were conducted using a questionnaire to assess demographic data and respiratory symptoms. Results: The mean concentration of RD and PM2.5 found in sandstone cutting was 0.48 and 0.25 mg/m3, while it was seen to be lower among sandstone chiselling (0.14 and 0.07 mg/m3). At least one respiratory symptom was reported by 57% of the workers. The most common symptom was phlegm (49.3%). Work experience and not wearing a mask while working were factors significantly associated with respiratory symptoms (p-values 0.018 and 0.014, respectively). Work experiences 6 -10 years and > 10 years, and not wearing masks had a chance of developing respiratory symptoms (OR=2.64, 2.73, and 2.73). Conclusion: PM2.5 accounted for half of the RD released during sandstone processing. Phlegm and dry cough were the most common symptoms among exposed workers. The workers should be advised to improve the working conditions and to use the appropriate masks. The local health authorities should establish routine monitoring of the working environment and an annual training course on dust prevention for workers.